Transformasi Budaya Madrasah dan Karakter Islami Melalui Kepemimpinan Transformasional di Era Digital: Studi Kasus MAS Islamiayah Sunggala Medan - Tumiran; Manshuruddin; Bahtiar Siregar; Dinda Mayani Pramudita (Medan Resource Center, 2025)
Madrasahs in the digital era face the dual challenge of preserving Islamic values while responding to rapid technological development. This study aims to examine the cultural transformation of the madrasah and the formation of Islamic character through transformational leadership at Madrasah Aliyah Swasta Islamiyah Sunggala Medan. Using a descriptive qualitative method with a case study design, data were collected through interviews, observations, and documentation involving principals, teachers, and students. Triangulation techniques were applied to ensure data validity. The findings reveal that transformational leadership effectively fosters an innovative and technology-adaptive madrasah culture by articulating a shared vision, empowering educators and learners, and encouraging collaborative practices. These cultural shifts contribute to the strengthening of students’ Islamic character, particularly in aspects of discipline and honesty. Nevertheless, challenges such as limited infrastructure and resistance to change remain significant barriers. This study highlights the essential role of transformational leadership in guiding madrasah transformation in the digital era.